Empirical determinants of saving in the Islamic banks: evidence from Indonesia - Kasri, Rahmatina Awaliah; Kassim, Salina (King AbdulAziz University, Kingdom Of Saudi Arabia, 2009)
This study attempts to determine the factors affecting saving in the Islamic banks in Indonesia. By employing the Vector Autoregressive and its associated Impulse Response Function analysis for all Islamic banks in Indonesia from March 2000 to August 2007, the study analyzes the importance of real rate of return on Islamic deposit, interest rate on conventional deposit, real income and number of Islamic bank branches in determining the level of savings in the Islamic banks. The results highlight the influential role of conventional interest rate in determining the level of saving in the Islamic banks. In particular, higher Islamic deposit is significantly correlated with higher rate of return and lower interest rate. Furthermore, the study finds the existence of displaced commercial risk between the Islamic and conventional banks, such that the Islamic banks’ depositors transfer their funds to the conventional banks when the rate of return provided by the Islamic banks is significantly lower that the interest rate of its counterpart. The findings of this study have important implication on the risk management practices in the Islamic banks in Indonesia.